Spatial distribution of human and canine visceral leishmaniasis in Belo Horizonte, Minas Gerais State, Brasil, 1994-1997 - Cláudia Di Lorenzo Oliveira; Renato Martins Assunção; Ilka Afonso Reis; Fernando Augusto Proietti
In this paper, we present spatial analysis of the association between all incidents cases of human Visceral Leishmaniasis and seropositive dogs, from 1994 to 1997 in Belo Horizonte, a large Brazilian city. We geocoded 158 human cases and 11,048 seropositive dogs and compared canine prevalence rates with Human Bayesian Incidence rates in the same areas. We also used Knox's test to evaluate the hypothesis of space-time clustering of human cases in the period. Additionally, we used Kernel's maps for seropositive dogs distribution and located the human cases in the resulting smooth maps. We concluded that human and dog rates are correlated. Also, the Visceral Leishmaniasis in Belo Horizonte spread quickly, but apart from the rates' magnitude, it has kept the same spatial pattern through time. We believe it is possible to use this technique to choose areas to implement control measures against Visceral Leishmaniasis in a more efficient way.